Yield Curve as a Predictor of Recessions: Evidence from Panel Data - Ozturk, Huseyin; Pereira, Luis Felipe V. N. (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2013)
In this study, we test empirically whether the slope of the yield curve-yield spread-is a good predictor of recessions. Although the convention in the literature is to use time series, we adopt an unbalanced panel data framework for thirty-two countries in the Organization for Economic Cooperation and Development from 1990 to 2011. This modification allows us to apply this model for countries with short time series. Furthermore, we include four-quarter lagged gross domestic product (GDP) in the model to assure that yield spread is a good predictor of recessions, even when controlling for GDP changes. The results show that with a type I error of 25 percent, the models deliver a power of roughly 63 percent and can be used as an effective instrument to predict recessions one year ahead.
Keywords: panel logit; panel probit; recession; term structure; BUSINESS FAILURE; RESPONSE MODELS; US RECESSIONS; VARIABLES; GROWTH; Business & Economics; International Relations